2014
DOI: 10.1074/jbc.m114.581702
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of Glutathione Peroxidase Mediates the Collateral Sensitivity of Multidrug-resistant Cells to Tiopronin

Abstract: Background: Tiopronin is a small molecule that selectively kills multidrug-resistant cancer cells. Results: Inhibition of glutathione peroxidase by tiopronin leads to elevated reactive oxygen species in MDR cells. Conclusion: Tiopronin mediates the killing of MDR cells by inhibition of glutathione peroxidases.Significance: Glutathione peroxidase inhibition may be a viable strategy for modulation of multidrug resistance in cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…Lorendeau et al [32] have recently published a comprehensive study on "classical" (i.e., not proto-) flavonoids' ability to selectively kill ABCC1 (MRP1)-transfected cancer cells through GSH depletion; potential use of protoflavones against such MDR cells might also be hypothesized. In addition to the role of oxidative stress in CS connected to the above-mentioned efflux transporters, Hall et al [1] demonstrated that, in P-gp overexpressing MDR cells obtained via adaptation, CS activity of the thiol-containing prescription drug tiopronin was mediated by ROS generation and the inhibition of glutathione peroxidase (GPx).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lorendeau et al [32] have recently published a comprehensive study on "classical" (i.e., not proto-) flavonoids' ability to selectively kill ABCC1 (MRP1)-transfected cancer cells through GSH depletion; potential use of protoflavones against such MDR cells might also be hypothesized. In addition to the role of oxidative stress in CS connected to the above-mentioned efflux transporters, Hall et al [1] demonstrated that, in P-gp overexpressing MDR cells obtained via adaptation, CS activity of the thiol-containing prescription drug tiopronin was mediated by ROS generation and the inhibition of glutathione peroxidase (GPx).…”
Section: Discussionmentioning
confidence: 99%
“…The impacts surgical intervention and/or radiotherapy. The capacity of cancer cells to develop resistance to chemotherapeutics is a significant challenge for new treatment strategies [1]. There is a wide range of cellular alterations acquired during the development of MDR: (1) overexpression of membrane efflux transporters belonging to the ATP-binding cassette family (e.g., the P-gp transporter, also known as P-glycoprotein or P-gp, which is the most prevalent among these so-called efflux pumps [2]), (2) extensively up-regulated DNA damage repair mechanisms, (3) impaired death signaling, (4) enhanced drug detoxification (e.g., up-regulation of glutathione-S-transferase enzymes), (5) lysosomal changes, (6) modification of drug molecular targets [3].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous reports detail increased GPX4 protein levels in the setting of genetic TXNRD1 perturbation. 33,34 To investigate this hypothesis, we assessed GPX4 protein levels in TXNRD1 -/cells through western blot, and confirmed higher GPX4 protein expression in these cells compared to WT ( Figure 3A). We also validated the ability of increased GPX4 protein levels to prevent ferroptotic cell death ( Figures 3B, S6, and S7).…”
Section: Inhibition Of Txnrd1 Does Not Protect Cancer Cells From Ferrmentioning
confidence: 92%
“…MDR cell lines expressing P-gp was explained by the inhibition of glutathionperoxidase (GPx) [73,74]. Another example is the natural product Austocystin D, which possesses increased toxicity against some MDR cell lines as a result of increased activation by cytochrome P450 [75].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%